Identification of potential molecular targets of luteolin in the treatment of hepatocellular carcinoma based on network pharmacology and transcriptome sequencing technology - Yunqi Han; Huijun Wu; Xin Zhang; Wei Lv; Yang Xiong; Xinyuan Tian; Yunfeng Xiao; Hongwei Cui (Discover Oncology)
Abstract Objective This study aims to identify potential target genes of luteolin (LUT) for treating hepatocellular carcinoma (HCC) through integrated in vitro experiments, network pharmacology, bioinformatics, and transcriptome sequencing (RNA-seq). Methods Potential LUT-associated therapeutic targets for HCC were predicted using network pharmacology. The anti-HCC effects of LUT were evaluated in vitro by assessing its impact on SMMC-7721 and HepG2 cell viability, apoptosis, migration, and invasion. Transcriptome sequencing was performed to identify differentially expressed genes (DEGs) in LUT-treated HepG2 cells, followed by bioinformatics analyses to validate hub targets and their associated pathways. Result Network pharmacology predicted 100 potential protein targets of LUT for HCC treatment, implicating pathways related to inflammation, cell migration, cell cycle regulation, and apoptosis, including the HIF-1α signaling axis. In vitro experiments demonstrated that LUT (40, 60, and 90 µmol·L−¹) significantly inhibited proliferation, induced apoptosis, and suppressed migration and invasion in SMMC-7721 and HepG2 cells. Transcriptome analysis identified 975 DEGs in LUT-treated HepG2 cells, with MMP9 and SRC emerging as key targets. Bioinformatics validation further linked LUT’s anti-HCC effects to cell cycle modulation, wound healing, enzyme inhibition, and the TNFα and HIF-1 signaling pathways. Conclusion LLUT suppresses HCC progression by inhibiting proliferation, regulating cell cycle and apoptosis, and blocking invasion and migration. Its therapeutic mechanisms likely involve targeting MMP9 and modulating the HIF-1α signaling pathway.